Can business schools use practical reasoning to help them with social impact? - John Paul Kawalek (Prometheus)
This paper concerns the challenges that face university-based business schools. These challenges are concerned with their ability to maintain expectations in educational and research terms, whilst at the same time making impact in social contexts. This paper outlines how impact might be informed by a heightened awareness of the difference between pure and practical reasoning. This was a key concern of Immanuel Kant, who laid the foundation of a philosophical genre which, in this paper, is termed ‘practical reasoning’. The paper contrasts some of the most fundamental ideas of practical reasoning with other forms used to underpin the activities of contemporary business schools. The paper presents an argument about how the methodological, epistemological and philosophical insights drawn from this genre may have relevance to the contemporary requirement for social impact in university-based business schools.